Cattle, seaweed, and global greenhouse gas emissions - Nin-Pratt, Alejandro; Beveridge, Malcolm C. M.; Sulser, Timothy B.; Marwaha, Nisha; Stanley, Michele; Grisenthwaite, Robert; Phillips, Michael J. (International Food Policy Research Institute, 2022)
This study is a first attempt to estimate the impact of a red seaweed (Asparagopsis taxiformis) feed additive on total emissions from cattle and the feasibility of scaling up farmed seaweed production to meet projected demand from the livestock sector. The approach used for the analysis combines projections of supply and demand of beef and milk production to 2050 with a cattle herd model that allows calculation of animal categories by age and sex, animal weight and production, and feed intake and methane emissions from cattle. At the time of this study, the seaweed additive showed limited applicability in grazing systems as it has been used experimentally, mostly incorporated in mix rations for each treatment animal, with not enough evidence available at present to determine the time of decay of the active component in seaweed after consumption by animals with limited access to the additive. Given these limitations, this study assumes that the applicability of the seaweed additive could be extended in the future to most dairy systems via slow-release formulations that have already been developed for other CH4 inhibitors and that can be fed daily during milking time. Based on this assumption, the maximum potential reduction of enteric methane emissions of the new technology is analyzed by projecting a scenario where the seaweed additive is supplied globally to dairy cows. Results show that the seaweed additive could result in a reduction of up to 10 percent in total methane emissions from cattle compared to a No-Seaweed scenario. Most of this reduction was driven by decreased emissions in Latin America, South Asia, and sub-Saharan Africa. The estimated reduction in feed intake associated with the seaweed additive was equivalent to an annual reduction in grain consumption of approximately 50 kgs per cow, or US$5 billion in global cost savings per year. The total amount of dry seaweed needed to supply dairy cows in 2050 was estimated at 5 million metric tons per year, representing 18 percent of the world’s seaweed-farmed area. Simply assuming the sector’s long-term historical average growth rates, this production level might be reached in approximately 20 years, although there are still several open questions about production and technologies and high variability in production costs and producer prices, as A. taxiformis is not extensively produced at present. Available knowledge on seaweed production seems to suggest that, at least at the start, production of A. taxiformis will be by nearshore culture. Expansion of nearshore culture could result in site competition with established seaweed production, access to operational license and government approvals in several countries, licenses to use livestock feeds incorporating seaweed as a feed additive, and more research to demonstrate the safety and efficacy of the additive in accordance with country’s regulations. The best possibilities for the development of production A. taxiformis seem to be in South Asia, for its growing demand and production of dairy products, its importance in terms of global emissions, and its location near the best- and well-established seaweed production areas in Southeast Asia.